Pengetahuan Remaja Putri tentang Terapi Musik Klasik sebagai Pengurangan Nyeri Menstruasi - Nurbaiti, Nurbaiti; Febrina, Ria; Perwitasari, Tuhu (Universitas Baiturrahim, 2024)
For young women, the incidence of dysmenorrhea is very disturbing in learning, they don't even take part in learning, it is difficult to concentrate because of the discomfort they feel during menstruation, emotional conflict, tension, anxiety, dysmenorrhea which is not treated immediately, it can result in disruption in daily activities or activities . One of the non-pharmacological treatments is the method of breathing relaxation and in combination with music. Music is an effective distraction technique where music can reduce physiological pain, stress and anxiety by distracting someone from pain. This study aims to determine the knowledge of young women about classical music therapy as a reduction in menstrual pain, this study uses a designdescriptive, conducted at Baiturrahim Jambi Vocational School, the population of all young women at Baiturrahim Vocational School totaling 139 students, the sample was taken using a total sampling technique. The results achieved in this study were mostly 15 year old respondents with 55 respondents (39.56%). While the knowledge of young women was obtained by the majority of respondents with sufficient knowledge of 88 (63.3%). The conclusion in this study is that the knowledge of young women is included in the sufficient category regarding the benefits of music therapy in reducing pain during menstruation (dyesmenorrhea). It is recommended that young women take part in activities that can provide knowledge, especially about music therapy in reducing pain during menstruation